2022
DOI: 10.1021/acsanm.2c04012
|View full text |Cite
|
Sign up to set email alerts
|

Netted C-Doped TiO2 Mesoporous Nanostructure Decorated by Cu Nanoparticles for Photocatalytic CO2 Reduction

Abstract: Acquiring an anatase TiO 2 catalyst with tiny size and high crystallinity for excellent photocatalytic performance still remains a huge challenge. Herein, a mesoporous C-doped TiO 2 netted nanostructure is successfully synthesized by a vacuum dipping and calcination method, where the thin film of multiwalled carbon nanotubes is skillfully utilized as the confinement template to suppress the grain growth and phase transfer. In addition, small Cu nanoparticles are deposited on the surfaces of the TiO 2 by an ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 71 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Photocatalytic H 2 generation via water splitting which can convert abundant solar energy into clean hydrogen is considered one of the most prosperous ways to settle the urgent universal energy crisis and environmental problems. , Since the original research reported in 1972, there have been many studies surveying different kinds of semiconductor materials for the photocatalytic reaction. Among those semiconductors, CdS has been demonstrated to possess great potential for photocatalytic energy conversion owing to its relatively narrow band gap (∼2.4 eV of bulk phase) and strong reduction ability (high-conduct band position). However, bare bulk CdS suffers from a low photocatalytic performance because of its confined external active sites, fast recombination of photo-produced charge carriers resulting from long charge migration distance, and low light absorption ability. …”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic H 2 generation via water splitting which can convert abundant solar energy into clean hydrogen is considered one of the most prosperous ways to settle the urgent universal energy crisis and environmental problems. , Since the original research reported in 1972, there have been many studies surveying different kinds of semiconductor materials for the photocatalytic reaction. Among those semiconductors, CdS has been demonstrated to possess great potential for photocatalytic energy conversion owing to its relatively narrow band gap (∼2.4 eV of bulk phase) and strong reduction ability (high-conduct band position). However, bare bulk CdS suffers from a low photocatalytic performance because of its confined external active sites, fast recombination of photo-produced charge carriers resulting from long charge migration distance, and low light absorption ability. …”
Section: Introductionmentioning
confidence: 99%